Electro-responsive actuators based on graphene - Yong-Lai Zhang (Elsevier, 2021)
Electro-responsive actuators (ERAs) hold great promise for cutting-edge applications in e-skins, soft robots, unmanned flight, and in vivo surgery devices due to the advantages of fast response, precise control, programmable deformation, and the ease of integration with control circuits. Recently, considering the excellent physical/chemical/mechanical properties (e.g., high carrier mobility, strong mechanical strength, outstanding thermal conductivity, high specific surface area, flexibility, and transparency), graphene and its derivatives have emerged as an appealing material in developing ERAs. In this review, we have summarized the recent advances in graphene-based ERAs. Typical the working mechanisms of graphene ERAs have been introduced. Design principles and working performance of three typical types of graphene ERAs (e.g., electrostatic actuators, electrothermal actuators, and ionic actuators) have been comprehensively summarized. Besides, emerging applications of graphene ERAs, including artificial muscles, bionic robots, human-soft actuators interaction, and other smart devices, have been reviewed. At last, the current challenges and future perspectives of graphene ERAs are discussed.